Safety climate at agricultural cooperatives. (December 2020) - Hanson, Erik; Boland, Michael
Abstract: Introduction: This study identifies determinants of safety climate at agricultural cooperatives. Methods: An extensive survey was designed to build upon past research done in collaboration with DuPont (Risch et al., 2014). In 2014 and 2015, the survey was administered to 1930 employees at 14 different agricultural cooperatives with 154 locations. Injury incidence data were also collected from each location to better understand the overall health and safety environment in this sector. An ordered probit model is used to identify variables that are associated with better safety climates. Results: Safety system components such as discipline programs, inspection programs, modified duty programs, off-the-job safety training programs, and recognition programs are positively related to individual safety climate for both managerial employees and nonmanagerial employees. Variables representing an employee's agricultural background, distance between their workplace and childhood home, and formal education are not associated with managerial safety climate. However, agricultural background and childhood home distance are associated with nonmanagerial safety climate. Conclusions: Improving occupational health and safety is a priority for many agricultural cooperatives. Lower safety climate emerges as nonmanagerial employees have more experience with production agriculture and work nearer to their home community. Practical applications: Employees of agricultural cooperatives face a host of health and safety challenges that are likely to persist into the future. The safety system components associated with safety climate indicate that continuous feedback is important for improving occupational health and safety. Occupational health and safety programming should also acknowledge that many employees have experiences that influence their attitudes and behaviors.